Animal experiments and network pharmacology to explore the anti-inflammatory mechanism of dapagliflozin in the treatment of polycystic ovary syndrome - Yong Liu; He Bai; Huilin Guan; Chunhua Wang; Xueqing Song; Zihao Yong; Xiaomeng Guo; Luxin Li; Zhen Zhang (Gynecological Endocrinology)
Background Polycystic ovary syndrome (PCOS) is a common endocrine and metabolic disorder associated with chronic low-grade inflammation of the ovary. Sodium glucose co-transporter 2 (SGLT2) inhibitors are a class of antidiabetic drugs that can reduce the weight and hyperglycemia of type 2 diabetes patients. Dapagliflozin is a highly selective, orally active and reversible inhibitor of the human SGLT2. However, the role of dapagliflozin in regulating PCOS remains unclear.Methods In this study, 24 six-week-old female Sprague Dawley (SD) rats were randomly divided into control, letrozole, and letrozole + dapagliflozin groups. PCOS model rats were produced by gavage administration of letrozole for 21 days. The intervention was conducted after the gavage administration of dapagliflozin for 14 days to evaluate the estrous cycle and ovarian imaging changes of the rats in each group. We observed changes in the weight, ovarian weight, and ovarian morphology of the rats in each group. Pathological changes in the ovaries were examined by H&E staining, changes in ovarian tissue cell apoptosis were identified using TdT-mediated dUTP Nick-End Labeling (TUNEL) staining, and changes in inflammation-related factors were detected using immunohistochemistry and Western blotting analysis. Network pharmacology was used to predict the inflammatory targets and pathways affected by dapagliflozin in treating PCOS, and the potential interactions between dapagliflozin and inflammation-related target proteins were evaluated through molecular docking.Results Our results demonstrated that dapagliflozin treatment significantly improved PCOS symptoms, recovered ovarian morphology and physiological functions, and reduced the apoptosis of ovarian cells after drug intervention. Dapagliflozin treatment also reduced the levels of pro-inflammatory cytokines such as IL-1β, IL-6, and TNF-α, indicating its anti-inflammatory properties. Furthermore, network pharmacology identified 26 intersecting target genes relevant to inflammation in PCOS, with subsequent molecular docking simulations revealing strong binding affinities of dapagliflozin to key targets, including AKT1 and TP53.Conclusions These findings suggest that dapagliflozin exerts beneficial effects on PCOS by ameliorating ovarian dysfunction and reducing inflammation. Dapagliflozin represents a promising therapeutic candidate for managing PCOS, warranting further clinical investigation to explore its full potential in treating this multifaceted disorder.